ECONOMIC EQUILIBRIUM: EMPIRICAL INSIGHTS INTO FISCAL SUSTAINABILITY AND MACROECONOMIC STABILITY IN TURKEY - Gültekin, Dr. Erkin (Economics and Statistics Research Journal (ESRJ), 2023)
In today's globalized and technologically advanced world, economies around the globe are deeply interconnected, leading to varying economic balances in both developed and emerging nations. Maintaining macroeconomic stability in these countries is crucial, and this brings us to the concept of sustainability. Sustainability, while lacking a precise definition in economics literature, generally encompasses the idea of ensuring the continuity and self-sufficiency of an economy. It goes beyond the stability of individual macroeconomic indicators, emphasizing the harmony and coherence between these indicators. Among the first concepts related to economic sustainability is fiscal sustainability. Fiscal sustainability, a frequently used term in economics, gained particular importance in economic policy planning during the 1990s. Although its definition lacks clarity, various perspectives exist. Buiter (1983) views fiscal sustainability as the implementation of policies that stabilize the net value of the budget deficit relative to GDP. In contrast, Blanchard et al. (1991) define it as achieving convergence of the Public Debt/GNP ratio to its initial level while ensuring the ability to service debt with public revenue. Edwards and Vergara (2002) suggest that fiscal sustainability exists when the Public Debt/GDP ratio remains stable and consistent with the overall demand in an economy. Analyzing the sustainability of the public sector involves calculating the primary balance required to maintain a sustainable and stable Public Debt/GDP ratio. Izquierdo and Panizza (2003) define fiscal sustainability as a country's capacity to meet its budget deficit. Among various methods to achieve balanced budget conditions, public debt is a widely employed strategy.